2018
DOI: 10.1007/s10337-018-3622-1
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the Band Broadening of UV Detectors used in Ultra-high Performance Liquid Chromatography using an On-tubing Fluorescence Detector

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 24 publications
(29 reference statements)
0
8
0
Order By: Relevance
“…Recent investigations by Dasgupta et al 95 . and Vanderlinden et al 96 . have shown that the dispersion contribution by the detector cell is also slightly affected by the applied flow rate, and is a function of flow cell volume.…”
Section: Uhplc Technologymentioning
confidence: 99%
“…Recent investigations by Dasgupta et al 95 . and Vanderlinden et al 96 . have shown that the dispersion contribution by the detector cell is also slightly affected by the applied flow rate, and is a function of flow cell volume.…”
Section: Uhplc Technologymentioning
confidence: 99%
“…The volumetric contribution of the detector cell to the total band broadening depends on the volume of the detector cell ( V cell ) and a constant characteristic of the UV cell geometry ( k cell ) (eq ). σ italicdet 2 = V c e l l 2 k c e l l The value k cell was previously reported to lie between 1 and 12, but for modern analytical ultrahigh performance liquid chromatography (UHPLC) systems with small volume cells, values around 1 are more realistic . The capillaries connecting the UV detector increase significantly the total length that a band eluting from a column has to pass to reach the mass spectrometer.…”
Section: Band and Peak Broadeningmentioning
confidence: 99%
“…Using a modified detector that allowed continuous variation of the cell path length and thus detection volume, it was recently clearly illustrated that flow cell dispersion is flow rate dependent unless very long path lengths are considered [95]. For short path lengths, the flow profiles at the inlet and outlet of the outlet of the detector start to make out the majority of the dispersion rather than the cell volume and det < 1 can easily be observed [95,96].…”
Section: Dispersion Arising From the Detectormentioning
confidence: 99%